Electrode protection layer based on carboxylated intrinsic microporous polymer and its manufacturing method

A crosslinked film formed from a carboxylated intrinsic microporous polymer and epoxy resin addresses the instability of lithium metal anodes by enhancing interface properties and suppressing dendrite growth, thereby improving battery stability and life.

JP2025514406AActive Publication Date: 2025-05-02KOREA RES INST OF CHEM TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024563931
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-04-25
Filing Date
2023-04-27
Publication Date
2025-05-02
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

The instability of lithium metal anodes in batteries due to the formation of sharp resinous lithium dendrites, which can lead to reduced battery efficiency and potential explosions, necessitates the development of a stable and effective protective layer.

Method used

A crosslinked film is produced by combining a carboxylated intrinsic microporous polymer with an epoxy resin, which is applied to the surface of the lithium metal anode, ensuring stable interface characteristics and suppressing the growth of resinous lithium dendrites.

Benefits of technology

The crosslinked film enhances the mechanical strength and interface properties between the lithium metal anode and the protective layer, leading to improved battery stability, extended life, and prevention of dendrite formation during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514406000001_ABST
    Figure 2025514406000001_ABST
Patent Text Reader

Abstract

The present invention relates to a carboxylated intrinsically microporous polymer-based electrode protection layer and a manufacturing method thereof, and more particularly to an intrinsically microporous polymer-based electrode protection layer manufactured by mixing a carboxylated intrinsically microporous polymer with a crosslinking agent and a solvent to prepare a film-forming composition, forming the composition into a film, and then crosslinking the film, and a manufacturing method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode protection layer based on carboxylated polymers of intrinsic microporosity and a method for preparing the same.

[0002] More specifically, the present invention relates to an intrinsically microporous polymer-based crosslinked polymer membrane electrode protection layer, which is prepared by mixing a carboxylated intrinsically microporous polymer with a crosslinking agent and a solvent to prepare a film-forming composition, applying the film-forming composition onto the surface of an electrode, and drying the solvent at room temperature to finally carry out a crosslinking reaction, and a method for manufacturing the same.

[0003] This application claims priority to Korean Patent Application No. 10-2022-0053793 filed on April 29, 2022 and Korean Patent Application No. 10-2023-0054353 filed on April 25, 2023, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0004] As the demand for large-capacity energy storage devices that can be used in electric vehicles, smart electronic devices, and drones increases, technologies using lithium metal as an anode material are being actively developed. When using lithium metal as an anode, the currently commercially available carbon-based anode (372 mAh g -1 ) compared to 3860mAhg -1 It exhibits a high theoretical capacity of 0.534 g cm at a low standard reduction potential (-3.04 V vs. standard hydrogen electrode (SHE)). -3 This is because it has a low density.

[0005] Due to these advantages, batteries using lithium metal as the anode were commercialized in the 1980s, but the instability of the lithium metal anode during use caused an explosion of the battery, leading to the recall of all batteries. Therefore, in order to commercialize secondary batteries that utilize the advantages of the lithium metal anode, it can be said that ensuring the stability of the lithium metal anode is the top priority.

[0006] The instability of lithium metal anodes is caused by the formation of lithium dendrites, which are sharp resin-like structures that are formed during charging and discharging. In particular, the unevenness of the solid electrolyte interphase (SEI) layer, which is a passive film that is naturally formed by the reaction with the electrolyte on the surface of the lithium metal anode during charging and discharging, causes local current density differences, and this variation in current distribution causes lithium metal to grow into sharp resin-like structures during charging. This resin-like lithium that grows in this way becomes dead lithium, which not only reduces the coulombic efficiency of the battery, but in the worst case, can cause an explosion due to an internal short circuit, making it a problem that must be solved to ensure the long life and stability of the battery.

[0007] In order to ensure the stability and long life of the lithium resin-like electrolyte, active research is being conducted on the introduction of artificial anode protection layers (artificial SEI), the introduction of new electrolytes and additives, the structural design of metal current collectors, the control of crystal nucleus growth, etc. Among them, the introduction of artificial anode protection layers is a method of introducing an SEI layer, which is a passive film that is favorable for lithium migration and interface properties, onto the surface of lithium metal, and mainly utilizes polymers that are favorable for lithium ion conduction and interface properties.

[0008] Such anode protection layers mainly contain various ion-conducting polymers such as poly(ethylene oxide) (PEO) and poly(propylene oxide) (PPO), which are representative lithium ion-conducting polymers. Poly(ethylene oxide) (PEO) polymers contain ether groups that can interact with lithium ions, and have a structure in which crystalline and amorphous regions coexist at room temperature. This polymer allows easy dissolution of lithium salts and migration of lithium ions due to the flexibility of the amorphous regions above the glass transition temperature, while the migration of lithium ions is restricted in the crystalline phase. As a result, PEO has a low melting point of 10 -8 ~10 -9 The reality is that PEO polymers are difficult to apply to commercial batteries because they exhibit low lithium ion conductivity at the non-conductive level of S / cm. Therefore, in order to develop PEO-based materials with high ionic conductivity, active research is being conducted to reduce the degree of crystallinity through approaches such as the introduction of organic and inorganic particles and plasticizers, increasing the lithium salt content, and producing copolymers. However, such efforts to reduce the degree of crystallinity can result in a decrease in mechanical properties, so in order to put PEO-based battery materials into practical use, results that simultaneously satisfy both ionic conductivity and mechanical properties are required.

[0009] In addition, materials such as covalent organic frameworks (COFs) and polymers of intrinsic microporosity (PIMs), which utilize micropores that are favorable for lithium ion movement, are also being actively researched. In particular, intrinsically microporous polymer (PIM) materials have a large number of micropores with a pore size of about 1 nm that are favorable for lithium ion movement, and can easily be applied to the surface of lithium metal through solution processing. Research on anode protection films using such intrinsically microporous polymers is being actively conducted, but there is a problem in that the interface characteristics between the intrinsically microporous polymer and the lithium metal anode are not good, resulting in the generation of empty spaces between the electrode and the polymer-based electrode protection layer. (See Korean Patent Publication No. 10-0542213, Korean Patent Publication No. 10-2017-0117649, Korean Patent Publication No. 10-2019-0033922, Korean Patent Publication No. 10-0655674, and Putintseva, MN, Yushkin, AA, Bondarenko, GNet al. Crosslinking of Polybenzodioxane PIM-1 for Improving Its Stability in Aromatic Hydrocarbons. Polym. Sci. Ser. B 61, 795-805 (2019)). When using a liquid electrolyte, the electrolyte may be consumed by the formation of an additional SEI layer and side reactions in such void spaces, so a polymer electrode protective film that can minimize and eliminate void spaces is required.

[0010] Therefore, the present inventors developed a lithium metal anode protective film that induces uniform movement of lithium ions by preparing a crosslinked film by introducing an epoxy resin into the carboxylated intrinsic porosity polymer according to the present invention. In addition, the anode protective film according to the present invention is an electrode protective layer that not only ensures stable interfacial characteristics between the metal surface and the electrode protective layer, but also suppresses resinous lithium dendrites that are generated during charging and discharging due to its high mechanical strength, unlike a case where only an intrinsic microporous polymer is used independently, by introducing an epoxy resin that is compatible with the lithium metal anode. This has led to the completion of the present invention. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Korean Patent No. 10-0542213 [Patent Document 2] Korean Patent Publication No. 10-2017-0117649 [Patent Document 3] Korean Patent Publication No. 10-2019-0033922 [Patent Document 4] Korean Patent No. 10-0655674 [Non-patent literature]

[0012] [Non-Patent Document 1] Polym.Sci.Ser.B 61, 795-805(2019) Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention has been developed to solve the above problems, and aims to provide an electrode protection layer based on a carboxylated intrinsic microporous polymer that has uniform lithium ion conductivity, excellent interfacial properties with lithium metal, and is capable of suppressing the formation and growth of lithium dendrites.

[0014] The present invention provides a novel method for producing a membrane that is different from conventional PIM-1 polymer-based IPN (Interpenetrating Polymer Network)-type crosslinked membranes and intrinsic microporous polymer-based ionically crosslinked membranes in terms of composition, production method, and application. [Means for solving the problem]

[0015] In order to solve the above problems, the present invention provides an electrode protection layer formed by reacting a homopolymer, copolymer, or mixture containing at least one of a compound represented by the following Chemical Formula 1 with a crosslinking agent to crosslink the homopolymer, copolymer, or mixture containing at least one of ... [ka] In Chemical Formula 1, X is any one selected from the group consisting of X1 to X17 below, and n is a repeating unit and is an integer of 10 to 500. [ka]

[0016] In an embodiment of the present invention, the crosslinker may have a chemical structure represented by Formula 2 below: [ka] In Chemical Formula 2, R is any one of a linear or branched alkylene group, a linear or branched alkylene group containing an oxygen atom, and an arylene group.

[0017] The present invention also provides a carboxylated intrinsic microporous polymer-based electrode protection layer, which is prepared by mixing a carboxylated intrinsic microporous polymer with an epoxy resin to prepare a composition, coating the prepared composition on the surface of an electrode, and then crosslinking the composition during drying.

[0018] The present invention also provides an electrochemical cell comprising an anode including the electrode protection layer, an electrolyte, and a cathode. Effect of the Invention

[0019] According to the present invention, a crosslinked membrane is prepared by a simple method by combining a carboxylated intrinsic microporous polymer with an epoxy compound, and the crosslinked membrane is then introduced onto the surface of lithium metal anode through a solution process, thereby ensuring the stability and long life of the lithium metal battery.

[0020] In addition, according to the present invention, uniform lithium ion movement can be facilitated by the micropores of the intrinsic microporosity and the ionic conductivity of the ion-conducting polymer, and excellent interfacial properties can be realized between the lithium metal battery and the polymer membrane through an appropriate combination of the intrinsic microporous polymer and the epoxy resin.

[0021] In addition, the present invention can suppress the growth of resinous lithium dendrites due to the excellent mechanical properties of the crosslinked membrane produced. Based on the properties of the crosslinked membrane based on the carboxylated intrinsic microporous polymer and epoxy resin described above, the battery life characteristics and stability in actual lithium symmetric cells or lithium full cells have been confirmed, and the effects are expected in commercial applications. [Brief description of the drawings]

[0022] [Figure 1] 1 shows the excellent interfacial properties of the crosslinked film for a lithium metal anode protective layer based on a carboxylated intrinsic microporous polymer prepared in an embodiment of the present invention. [Diagram 2] 1 is a graph showing the experimental results of a lithium symmetric cell using a lithium metal anode with or without a carboxylated intrinsic microporous polymer-based crosslinked membrane prepared in an embodiment of the present invention; [Diagram 3]1 shows the results of electrochemical impedance spectroscopy experiments (measurement of ionic conductivity and lithium ion mobility) for a lithium symmetric cell prepared using a lithium metal anode incorporating a carboxylated intrinsic microporous polymer-based crosslinked membrane prepared in accordance with an embodiment of the present invention. [Figure 4] 1 shows the results of electrochemical impedance spectroscopy experiments (measurement of ionic conductivity and lithium ion mobility) for a lithium symmetric cell prepared using a lithium metal anode incorporating a carboxylated intrinsic microporous polymer-based crosslinked membrane prepared in accordance with an embodiment of the present invention. [Diagram 5] 1 shows the results of testing the capacity change and long-term performance according to the charge / discharge rate for a full cell of a lithium metal secondary battery prepared using a lithium metal anode incorporating a carboxylated intrinsic microporous polymer-based crosslinked membrane prepared in an embodiment of the present invention and a Ni83 cathode. [Figure 6] 1 shows the results of testing the capacity change and long-term performance according to the charge / discharge rate for a full cell of a lithium metal secondary battery prepared using a lithium metal anode incorporating a carboxylated intrinsic microporous polymer-based crosslinked membrane prepared in an embodiment of the present invention and a Ni83 cathode. [Figure 7] 1 shows the results of testing the capacity change and long-term performance according to the charge / discharge rate for a full cell of a lithium metal secondary battery prepared using a lithium metal anode incorporating a carboxylated intrinsic microporous polymer-based crosslinked membrane prepared in an embodiment of the present invention and a Ni83 cathode. [Figure 8] 1 shows the results of observing the interface characteristics through SEM after casting PIM-COOH (without PEO) on a copper foil that can be used as a current collector of a battery according to an embodiment of the present invention. [Figure 9] After casting PIM-COOH and PEO-based epoxy resin compositions (PIM-COOH:PEO (1:1)) onto copper foil, which can be used as a battery current collector, the interfacial characteristics were confirmed using a SEM. [Figure 10]1 shows the results of a comparison test to clarify the difference between the conventional PIM-1 polymer-based interpenetrating polymer network and the present invention. [Figure 11] 1 shows the results of a comparison test to clarify the difference between the conventional PIM-1 polymer-based interpenetrating polymer network and the present invention. [Figure 12] 1 shows an XRD result for a PIM-COOH and PEO-based epoxy resin composition according to an embodiment of the present invention. [Figure 13] 1 shows a DSC result for PIM-COOH and PEO-based epoxy resin compositions according to an embodiment of the present invention. [Figure 14] This is the result of confirming the reaction between methanol, which is used as a solvent for the crosslinker solution, and lithium metal, which corresponds to the battery anode, in the conventional PIM-1 polymer-based interpenetrating polymer network. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present invention will be described in detail below with reference to examples. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, in accordance with the principle that the inventors themselves can appropriately define the concepts of terms in order to best describe the invention.

[0024] The "Polymers of Intrinsic Microporosity (PIM)" according to the present invention are polymers that have a twisted structure skeleton, and thus the polymer structure is not densely packed, resulting in a large amount of microporosity. According to the definition of IUPAC (International Union of Pure and Applied Chemistry), porous materials are classified into micropores (pore size < 2 nm), mesopores (pore size 2 nm < 50 nm), and macropores (pore size > 50 nm) according to the pore size. The porous material containing the intrinsic porosity polymer according to the present invention mainly contains micropores of less than 2 nm, although micropores and mesopores may coexist.

[0025] The crosslinked membrane based on a carboxylated intrinsic microporous polymer according to the present invention is prepared by mixing a carboxylated intrinsic microporous polymer and an epoxy resin as a crosslinker in a solution state and casting the mixture in a solution. It is classified from the conventional PIM-1 polymer-based IPN (Interpenetrating Polymer Network) type crosslinked membrane and the ion crosslinked membrane prepared by reacting a carboxylated intrinsic microporous polymer with an aluminum ion (Polym. Sci. Ser. B 61, 795-805 (2019)) in terms of preparation method and application. The crosslinked membranes prepared by the above two methods were applied as an example of application for separation of aromatic hydrocarbons.

[0026] First, in the case of the conventional PIM-1 polymer-based interpenetrating polymer network, unlike the reaction of PIM-COOH and epoxy resin as a crosslinker according to the present invention, not only is it not possible to induce a direct reaction between PIM-1 and the crosslinker, but also it is different in that in order to manufacture the PIM-1-based interpenetrating polymer network, poly(ethyleneimine) is first impregnated into the inside of PIM-1, and then a crosslinking reaction between poly(ethyleneimine) and epoxy resin is induced. That is, the present invention is distinguished from the conventional technology in that it is not only possible to realize a crosslinked membrane by only combining two types of intrinsic microporous polymer and epoxy resin as a crosslinker, but also easy to adjust the ratio of PIM and crosslinker.

[0027] The present invention also differs from the prior art in terms of its composition. The composition according to the present invention is a one-part type in which the resin and the crosslinker coexist in a solution state, whereas the prior art corresponds to a two-part type in which solutions containing the resin and the crosslinker are stored separately and then mixed in a subsequent step for reaction. In most industrial fields, there is a demand for the development of one-part compositions instead of two-part compositions in order to make it easier to use epoxy resins under various conditions. Similarly, the composition according to the present invention is a one-part composition that simultaneously contains the resin and the crosslinker, which is a technology that allows for uniform coating and optimization of the coating layer, and is easier to manufacture in the form of a one-part composition in which crosslinking does not occur in the solution.

[0028] In particular, in the case of a two-component type in which the resins and crosslinking agents are stored separately, there is a high possibility that the chemical composition of the composition will vary when the solutions are mixed on-site, resulting in non-uniform physical properties of the final crosslinked product. However, since the film produced by the present invention is a one-component type, it has a uniform composition and is very easy to adjust the thickness, making it easy to realize a film with uniform physical properties, and therefore can demonstrate superior performance in terms of storage, application, and final physical properties compared to conventional technologies.

[0029] Next, in the case of the conventional PIM-1 polymer-based interpenetrating polymer network, when a membrane is manufactured through ionic crosslinking between PIM-COOH and divalent or trivalent ions (e.g., aluminum ions), a PIM-1 polymer membrane is first manufactured, and the manufactured polymer membrane is hydrolyzed to a point where the membrane shape can be maintained, to manufacture a PIM-COOH polymer membrane. For reference, hydrolysis to a point where the shape can be maintained only provides a carboxylated intrinsic microporous polymer with a low conversion rate of 50% or less, while in the present invention, PIM-COOH with a high conversion rate of 90% or more is manufactured, and then a membrane is manufactured through a solution process, so that the membrane manufacturing method can be distinguished.

[0030] In addition, in the prior art, a method is used in which a membrane is prepared, and then the membrane is immersed in an aluminum chloride (AlCl3) solution to induce ion exchange, thereby preparing a PIM-COOH-based ion-crosslinked membrane. That is, this method is a method in which a polymer membrane is first prepared, and then an ion-crosslinked membrane is finally prepared through ion exchange, which is fundamentally different from the method proposed by the present invention in which an electrode protection layer is directly introduced on the surface of lithium through solution casting. More specifically, in the case of a polymer membrane prepared through ion crosslinking, since its solubility in an organic solvent is limited, it is difficult to directly introduce an electrode protection layer in a solution process, and a conventionally prepared membrane must be introduced on the surface of the electrode, which inevitably results in the formation of an empty space at the interface between the electrode and the electrode protection layer. In contrast, the solution composition prepared by the present invention is directly introduced on the surface of the electrode, thereby improving the interface characteristics.

[0031] In addition, when the membrane manufactured by the conventional technology is applied to the field of batteries, there is a disadvantage that aluminum ions randomly introduced into the anode protective layer due to ion crosslinking and residual aluminum chloride solution may cause side reactions such as lithium-aluminum alloy reaction in the battery during operation of the electrode.

[0032] Therefore, in order to solve the above problems, the present invention provides an electrode protection layer formed by reacting a homopolymer, copolymer, or mixture containing at least one of the above compounds represented by the following Chemical Formula 1 with a crosslinking agent to crosslink the homopolymer, copolymer, or mixture containing at least one of the above compounds: [ka] In Chemical Formula 1, X is any one selected from the group consisting of X1 to X17 below. [ka]

[0033] In an embodiment of the present invention, the crosslinker may have a chemical structure represented by Formula 2 below. [ka] In Chemical Formula 2, R is any one of a linear or branched alkylene group, a linear or branched alkylene group containing an oxygen atom, and an arylene group.

[0034] In one embodiment of the present invention, in Formula 2, R may be any one of the following formulas: -(CH2) m -, -(CH2) m -O-(CH2) l -, -(CH2) m -O-(CH2) l -, -CH2-O-(CH2)4-O-CH2- [ka] Here, m and l are the same or different and are integers of 1 to 6, and n is an integer of 1 to 10,000.

[0035] In an embodiment of the present invention, the electrode protection layer may have a thickness of 10 nm to 300 μm.

[0036] The present invention also provides an electrode comprising an anode and an electrode protection layer according to any one of claims 1 to 13 coated on the anode.

[0037] In one embodiment of the present invention, the anode may be capable of storing and releasing lithium ions, and may be at least one selected from the group consisting of Li, Na, K, Mg, Ca, Zn, Al, Si, Ge, Sn, and alloys thereof.

[0038] The present invention also provides an electrochemical cell comprising the anode, an electrolyte, and a cathode.

[0039] In an embodiment of the present invention, the fuel cell may further include a separator between the anode and the cathode.

[0040] The present invention also provides a method for forming an electrode protection layer, the method including the steps of: preparing an anode; providing a polymer, which is a homopolymer, a copolymer, or a mixture containing at least one of the above-mentioned compounds represented by Chemical Formula 1 below; preparing a film-forming composition by mixing the polymer, a crosslinker, and a solvent; forming a film on the anode using the film-forming composition; and preparing a crosslinked polymerized film by crosslinking the film. [ka] In Chemical Formula 1, X is any one selected from the group consisting of X1 to X17 below, and n is a repeating unit and is an integer of 10 to 500. [ka]

[0041] In an embodiment of the present invention, the crosslinker may have a chemical structure represented by Formula 2 below. [ka] In Chemical Formula 2, R is any one of a linear or branched alkylene group, a linear or branched alkylene group containing an oxygen atom, and an arylene group.

[0042] In one embodiment of the present invention, in Formula 2, R may be any one of the following formulas: -(CH2) m -, -(CH2) m -O-(CH2) l -, -(CH2) m -O-(CH2) l -, -CH2-O-(CH2)4-O-CH2- [ka] Here, m and l are the same or different and are integers of 1 to 6, and n is an integer of 1 to 10,000.

[0043] In one embodiment of the present invention, the solvent may be at least one selected from the group consisting of tetrahydrofuran (THF), N-methylpyrrolidone (NMP), dimethylsulfoxide (DMSO), dimethylformamide (DMF) and dimethylacetamide (DMAc).

[0044] In one embodiment of the present invention, the step of crosslinking the membrane to prepare a crosslinked polymer membrane may be carried out through the reaction of Reaction Scheme 1 below. [ka] In the above reaction formula 1, n is a repeating unit and is an integer of 10 to 500, and R is any one of a linear or branched alkylene group, a linear or branched alkylene group containing an oxygen atom, and an arylene group.

[0045] Hereinafter, preferred embodiments and examples of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily carry out the present invention. However, the technical idea of ​​the present invention and its core configuration and operation are not limited thereto. In addition, the contents of the present invention can be realized in various types of devices and are not limited by the embodiments and examples described herein.

[0046] <Production Example 1> Production of polymer with inherent microporosity (PIM) After removing moisture from the inside of a two-necked round-bottom flask (250 ml), 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane (TTSBI) (10.21 g, 30 mmol), K2CO3 (8.29 g, 60 mmol), tetrafluorophthalonitrile (TFTPN) (6.00 g, 30 mmol), and dimethylformamide (DMF) (210 ml) were added to the flask under a nitrogen atmosphere, and polymerization was carried out at 55°C for 72 hours. After the reaction was completed, 350 ml of tetrahydrofuran (THF) was added to the reactor cooled to room temperature to precipitate PIM-1, which has a high molecular weight, and the supernatant containing low molecular weight and oligomers was removed. The polymer was redissolved in tetrahydrofuran (THF) and reprecipitation was repeated twice using methanol. The final product was dried in a vacuum to obtain a yellowish intrinsic microporous polymer (PIM-1) (10.3 g) represented by the following chemical formula 3. GPC (Gel Permeation Chromatography) measurement showed that M n = 60,900 and PDI (Polydispersity index) 1.58. [ka]

[0047] <Preparation Example 2> Preparation of carboxylated intrinsically microporous polymer (PIM-COOH) A 20 wt% NaOH solution was prepared by adding 480 ml of distilled water, 600 ml of ethanol, and 240 g of NaOH to a three-necked round-bottom flask (2000 ml), and then the inherently microporous polymer (PIM-1) obtained in Preparation Example 1 was added and modified at 125°C for 360 hours. After the reaction was completed, the mixture was left to stand so that the aqueous layer and the organic layer were separated using a liquid-liquid separator, and the organic layer containing the modified inherently microporous polymer was separated and slowly precipitated in about 5 wt% HCl solution and filtered. After washing several times with distilled water, the filtrate was dried in a vacuum dryer at a temperature of 60°C for 24 hours, dissolved in tetrahydrofuran (THF), and re-precipitated twice using water and methanol. The final product was vacuum-dried to obtain a yellowish carboxylated inherently microporous polymer (PIM-1) (7.0 g) of the following chemical formula 4. As a result of GPC measurement, M n = 25,700, PDI 1.07. [ka]

[0048] Example 1: Preparation of polymer crosslinked membrane for lithium metal anode protection layer containing carboxylated intrinsic microporous polymer To prepare a polymer crosslinked membrane for the anode protective layer, the carboxylated intrinsically microporous polymer (PIM-COOH) prepared in Preparation Example 2 and poly(ethylene glycol) diglycidyl ether (Mn = 500) were mixed in mass ratios of 1:2, 1:1, and 2:1. Tetrahydrofuran (THF) was added to the mixture to adjust the concentration of the solution to 12.5 mg mL -1 The prepared polymer solution was applied onto lithium metal while filtering out impurities with a 5μm syringe filter. To remove the solvent from the applied polymer solution, it was dried at room temperature for more than 12 hours. All processes were carried out in a glove box filled with argon. Using the above method, a polymer crosslinked membrane for the anode protection layer with a thickness of 10μm to 100μm was prepared, which contains a carboxylated intrinsic microporous polymer.

[0049] Comparative Example 1: Preparation of carboxylated intrinsically microporous polymer membrane To prepare a carboxylated intrinsically microporous polymer crosslinked membrane, PIM-COOH prepared in Preparation Example 2 and tetrahydrofuran (THF) were used to prepare a carboxylated intrinsically microporous polymer crosslinked membrane with 12.5 mg mL -1 A polymer solution with a concentration of 100 μm was prepared. The prepared polymer solution was applied onto lithium metal while filtering out impurities with a 5 μm syringe filter. The solvent was slowly evaporated in air for two days, and the dried film was separated from the glass Petri dish. It was then dried for 24 hours in a vacuum dryer adjusted to 100°C. Using the above method, a polymer membrane with a thickness of 10 μm to 100 μm and inherent carboxylated micropores was prepared.

[0050] <Analysis Example 1> Lithium (Li-Li) Symmetric Cell Test Two lithium metal electrodes coated with the polymer crosslinked membrane containing the carboxylated intrinsically microporous polymer prepared in Example 1 according to the present invention were assembled in a 2032 coin cell type (performed in an argon glove box) using Celgard 2500 and an ethylene carbonate (EC):diethyl carbonate (DEC) (1:1, v / v%) electrolyte containing 1M LiPF6 containing fluoroethylene carbonate (FEC, 10 w / w%) and vinylene carbonate (VC, 1 w / w%).

[0051] <Analysis Example 2> Measurement of ionic conductivity and lithium ion mobility Electrochemical impedance spectroscopy (EIS) was performed in the range of 300 kHz to 1 Hz. Li-Li symmetric cells were fabricated with lithium electrodes with or without the PIM-COOH / PEO crosslinked film and experiments were performed.

[0052] <Analysis Example 3> Electrochemical experiment of lithium full cell The lithium metal electrode coated with the polymer crosslinked membrane containing the carboxylated intrinsic microporous polymer prepared in Example 1 according to the present invention was used as the anode, and Ni83 was used as the cathode material to assemble a 2032 coin cell type (performed in an argon glove box). Charge and discharge experiments were performed in the voltage range of 3.0 to 4.3 V using a charger and discharger.

[0053] FIG. 1 shows the interfacial properties of the crosslinked membrane for lithium metal anode protection layer based on a carboxylated intrinsic microporous polymer prepared in an embodiment according to the present invention. The samples shown in FIG. 1 are as follows: (a) PIM-1, (b) PIM-COOH, (c) PIM-1:PEO(1:2), (d) PIM-COOH:PEO(2:1), (e) PIM-COOH:PEO(1:1), (f) PIM-COOH:PEO(1:2). In the case of (a) PIM-1 and (b) PIM-COOH, the corresponding solution was applied to the surface of the electrode and the solvent was dried at room temperature, but no crosslinking was induced. (c) PIM-1:PEO(1:2) membrane is a membrane prepared by the above method, but unlike the (d) to (f) samples, it is a mixed membrane of PIM-1 and PEO epoxy that was simply mixed without crosslinking. In this case, unlike the film that induced crosslinking, the phenomenon that the film for the anode protection layer detached from the electrode was observed. Samples (d) to (f) are films that induced crosslinking by mixing PIM-COOH and a PEO-based epoxy compound in weight ratios of 2:1, 1:1, and 1:2, respectively, applying them to the surface of the electrode, and drying the solvent at room temperature.

[0054] Referring to Figure 1, it can be seen that peeling occurs in the case of the PIM-1 material that has not been modified. On the other hand, in the case of the crosslinked membrane prepared from the carboxylated intrinsic microporous polymer or a combination of the same with an epoxy resin, excellent interfacial properties are exhibited and no peeling phenomenon is observed. Therefore, a polymer crosslinked membrane having optimized interfacial properties with a lithium metal anode can be prepared by using the carboxylated intrinsic microporous polymer or a combination of the same with an epoxy resin.

[0055] 2 is a graph showing the experimental results of a lithium symmetric cell using a lithium metal anode with or without a crosslinked membrane based on a carboxylated intrinsic microporous polymer prepared in an embodiment according to the present invention. In FIG. 2, COOH:PEO (1:2), (1:1) and (2:1) respectively refer to crosslinked membranes prepared by mixing a carboxylated intrinsic microporous polymer (PIM-COOH) and poly(ethylene glycol) diglycidyl ether (Mn=500) in a mass ratio of 1:2, 1:1 and 2:1, and COOH refers to the carboxylated intrinsic microporous polymer (PIM-COOH).

[0056] Figure 2 shows that the crosslinked membrane shows superior long-term life characteristics in the lithium symmetric cell results compared to the carboxylated intrinsic microporous polymer crosslinked membrane (-COOH) that is not crosslinked with epoxy resin (poly(ethylene glycol) diglycidyl ether; PEO). This is believed to be because, as seen in Figure 1, the polymer membrane has excellent interfacial properties with the lithium metal anode due to the carboxyl and hydroxyl groups contained in the polymer membrane, so peeling or additional side reactions due to peeling do not occur during battery operation.

[0057] 3 and 4 show the results of measuring the ionic conductivity and the lithium ion mobility by electrochemical impedance spectroscopy for a lithium symmetric cell prepared using a lithium metal anode having a crosslinked membrane prepared by mixing a carboxylated intrinsic microporous polymer and poly(ethylene glycol) diglycidyl ether in a mass ratio of 2:1 as a protective layer, the crosslinked membrane being prepared according to an embodiment of the present invention.

[0058] As can be seen from Figures 3 and 4, the carboxylated intrinsic microporous polymer-based crosslinked membrane is composed of a combination of micropores that are favorable for lithium ion movement and a polymer that allows ion movement, and therefore shows a high lithium ion mobility of 0.67, which is superior to the lithium ion mobility of about 0.2 to 0.4 observed in commercial liquid electrolytes. The carboxylated intrinsic microporous polymer-based crosslinked membrane, which has such high lithium ion mobility, allows for uniform electrical application and lithium ion movement rather than localized electrical application even during high-speed charging and discharging due to fast lithium ion movement.

[0059] 5 to 7 show the results of testing the capacity change and long-term performance according to the charge / discharge rate for a lithium metal secondary battery full cell fabricated using a lithium metal anode and a Ni83 cathode, in which a crosslinked membrane prepared by mixing a carboxylated intrinsic microporous polymer and poly(ethylene glycol) diglycidyl ether in a mass ratio of 2:1, 1:1, and 1:2, which are prepared according to an embodiment of the present invention, is introduced as a protective layer. From FIG. 5, it can be seen that the introduction of the crosslinked membrane based on the carboxylated intrinsic microporous polymer does not cause a large capacity decrease even during high-speed charge / discharge. This is believed to be because lithium ions move smoothly through the introduced crosslinked membrane. Also, from FIG. 6, it can be seen that the capacity does not decrease significantly even after more than 100 charge / discharge cycles. From the performance results of the full cell in FIG. 7, it can be seen that the cell having the electrode protective membrane introduced has excellent capacity retention characteristics and coulombic efficiency compared to the lithium metal anode without the crosslinked membrane. This is believed to be because the introduced crosslinked film protects the lithium metal anode and suppresses side reactions with the electrolyte that occur during battery operation and capacity loss due to dead lithium.

[0060] 8 and 9 show the results of observing the interface characteristics by SEM after casting PIM-COOH (without PEO) and an epoxy resin composition based on PIM-COOH and PEO (PIM-COOH:PEO (1:1)) on a copper foil that can be used as a current collector of a battery according to an embodiment of the present invention. When a solution composition consisting of only PIM-COOH (PIM-COOH (without PEO)) without introducing an epoxy resin is solution cast, as can be seen from FIG. 8, a large empty space can be observed between the polymer film and the copper foil. On the other hand, in FIG. 9, by additionally introducing an epoxy resin (PIM-COOH:PEO (1:1)), no empty space can be observed between the copper foil and the polymer electrode protection film. In other words, by introducing a PEO-based epoxy resin, excellent interface characteristics that could not be achieved by using only a conventional intrinsic microporous polymer can be achieved.

[0061] 10 and 11 are the results of a comparison test to clarify the difference between the conventional PIM-1 polymer-based interpenetrating polymer network and the present invention. A PIM-COOH polymer film was first produced by a solution casting method, and then a divalent cation (Cu 2+ , Ni 2+ , Zn 2+ The samples shown in Figure 10 are as follows: (a) PIM-COOH, (b) PIM-COOH·Cu complex, (c) PIM-COOH·Ni complex, and (d) PIM-COOH·Zn complex.

[0062] As can be seen from Figure 11, the polymer crosslinked membrane where ion crosslinking is completed is difficult to dissolve using a solvent such as THF. This means that the conventional method of manufacturing a PIM-COOH-based ion crosslinked membrane by inducing ion exchange by putting the film in an aluminum chloride (AlCl3) solution after manufacturing the membrane is limited in manufacturing an electrode protective membrane through a solution casting method performed after dissolving the polymer composition proposed in the present invention.

[0063] Figure 12 shows the XRD results for the PIM-COOH and PEO-based epoxy resin composition according to an embodiment of the present invention. It is generally known that in the case of pure PEO, two strong peaks for (120) and (112) appear at 19.36 and 23.72°. However, as can be seen from Figure 12, no peaks due to PEO crystallization are observed in the results for the PIM-COOH and PEO-based epoxy resin composition. This means that the PEO chains in the PIM-COOH and PEO-based epoxy resin composition are not in a crystalline form that inhibits lithium ion migration, but in an amorphous form that favors lithium migration.

[0064] Figure 13 shows the DSC results for PIM-COOH and PEO-based epoxy resin compositions according to an embodiment of the present invention. As can be seen from Figure 13, in the case of pure PEO (PEO 200K), a dissolution peak due to the contained crystals is observed at 62.8°C, while in the case of PIM-COOH and PEO-based epoxy compositions, no dissolution peak due to PEO is observed. This means that in the PIM-COOH and PEO-based epoxy compositions, as confirmed by the XRD results, PEO does not form crystals in the polymer composition.

[0065] FIG. 14 shows the reaction between methanol used as a solvent for the crosslinker solution and lithium metal, which corresponds to the anode of a battery, in a conventional PIM-1 polymer-based interpenetrating polymer network.

[0066] In the case of the conventional PIM-1 polymer-based interpenetrating polymer network, methanol is used to dissolve the epoxy resin. However, if such a conventional method is used to manufacture a protective layer for lithium metal, which is the anode of a battery, a violent reaction occurs between methanol and lithium metal, corroding the lithium metal and forming an irreversible form of lithium methoxide. Therefore, the membrane manufacturing method described in the conventional method cannot be directly applied in the field of batteries.

Claims

1. The following chemical formula 1: 【Chemistry 1】 An electrode protection layer formed by reacting a homopolymer, copolymer, or mixture containing one or more of the above-mentioned compounds with a crosslinking agent to crosslink the compound, In the formula 1, X is any one selected from the group consisting of X1 to X17: 【Chemistry 2】

2. The crosslinking agent is represented by the following formula 2: 【Chemistry 3】 having the chemical structure The electrode protection layer according to claim 1 , wherein in Chemical Formula 2, R is any one of a linear or branched alkylene group, a linear or branched alkylene group containing an oxygen atom, and an arylene group.

3. In formula 2, R is represented by the following formula: -(CH 2 ) m -、 -(CH 2 ) m -O-(CH 2 ) l -、 -(CH 2 ) m -O-(CH 2 ) l -、 -CH 2 -O-(CH 2 ) 4 -O-CH 2 -、 【Chemistry 4】 One of the following:

3. The electrode protection layer according to claim 2, wherein m and l are the same or different and each is an integer of 1 to 6, and n is an integer of 1 to 10,000.

4. An anode; and an electrode protection layer according to claim 1 coated on the anode.

5. 5. The electrode of claim 4, wherein the anode is capable of storing and releasing lithium ions.

6. 5. The electrode of claim 4, wherein the anode is one or more selected from the group including Li, Na, K, Mg, Ca, Zn, Al, Si, Ge, Sn, or alloys thereof.

7. An electrode according to any one of claims 4 to 6 as an anode; An electrolyte; a cathode.

8. 8. The electrochemical cell of claim 7 further comprising a separator between the anode and cathode.

9. providing an anode; The following chemical formula 1: 【Chemistry 5】 providing a polymer, a homopolymer, a copolymer, or a mixture containing at least one of the above, of a compound represented by the formula: preparing a film-forming composition by mixing the polymer, a crosslinker and a solvent; forming a film on the anode using the film-forming composition; a cross-linking polymer membrane preparation step of cross-linking the membrane; Including, In Chemical Formula 1, X is any one selected from the group consisting of X1 to X17 below, and n is a repeating unit and an integer of 10 to 500. 【Chemistry 6】 。

10. The crosslinking agent is represented by the following formula 2: 【Chemistry 7】 having the chemical structure 10. The method for forming an electrode protection layer according to claim 9, wherein in Chemical Formula 2, R is any one of a linear or branched alkylene group, a linear or branched alkylene group containing an oxygen atom, and an arylene group.

11. In formula 2, R is represented by the following formula: -(CH 2 ) m -、 -(CH 2 ) m -O-(CH 2 ) l -、 -(CH 2 ) m -O-(CH 2 ) l -、 -CH 2 -O-(CH 2 ) 4 -O-CH 2 -、 【Chemistry 8】 One of the following:

10. The method for forming an electrode protection layer according to claim 9, wherein m and l are the same or different and are integers of 1 to 6, and n is an integer of 1 to 10,000.

12. 10. The method for forming an electrode protection layer according to claim 9, wherein the solvent is at least one selected from the group consisting of tetrahydrofuran (THF), N-methylpyrrolidone (NMP), dimethylsulfoxide (DMSO), dimethylformamide (DMF) and dimethylacetamide (DMAc).

13. The step of crosslinking the membrane to prepare a crosslinked polymer membrane is carried out according to the following reaction scheme 1: 【Chemistry 9】 This is carried out through the reaction 10. The method for forming an electrode protection layer according to claim 9, wherein in Reaction Scheme 1, n is a repeating unit and is an integer of 10 to 500, and R is any one of a linear or branched alkylene group, a linear or branched alkylene group containing an oxygen atom, and an arylene group.

Citation Information

Patent Citations

  • Coated negative electrode active material for lithium ion battery

    JP2017188451A

  • Negative electrode for lithium ion secondary battery and lithium ion secondary battery using the same

    JP2018049825A

  • Lithium anode protective polymer layer for lithium metal secondary batteries and method of manufacture

    JP2020517056A

  • Acid-resistant base and / or radical generator, and curable resin composition containing said base and / or radical generator

    WO2017018361A1

  • Negative electrode of lithium metal battery and lithium metal battery comprisng same

    KR100542213B1